Psychometric properties of the DSM‐5 social anxiety disorder dimensional scale in an Australian community sample. Issue 5 (26th October 2021) - Binasis, Theodora; Groves, David; Wootton, Bethany M.; Moses, Karen
Abstract: Objective: The Social Anxiety Disorder Dimensional Scale (SAD‐D) is a 10‐item scale developed by the Diagnostic and Statistical Manual (Fifth Edition) Anxiety, Obsessive‐Compulsive Spectrum, Posttraumatic, and Dissociative Disorder work group to supplement current dichotomous approaches to assessment of Social Anxiety Disorder (SAD). The aim of the present study was to evaluate the psychometric properties of the SAD‐D in an Australian community sample. Methods: Two‐hundred and ninety‐one participants (72.9% female) aged 18‐76 years ( M =28.46; SD = 12.30) completed the study. Results: Confirmatory factor analysis indicated support for the unidimensional structure of the SAD‐D (root mean square error of approximation [RMSE] = 0.08; comparative fit index [CFI] = 0.97). The measure demonstrated strong internal consistency ( α = 0.94), as well as good divergent validity. The SAD‐D showed excellent test‐retest reliability (intraclass correlation coefficient [ICC] = 0.93). Conclusions: Overall, the SAD‐D appears to be a brief and reliable measure of SAD symptomatology. Limitations, including the use of a predominantly female convenience sample, and failure to include the mental health and background of the sample, are discussed.